1992
DOI: 10.7146/dpb.v21i383.6615
|View full text |Cite
|
Sign up to set email alerts
|

An Automatically Generated and Provably Correct Compiler for a Subset of Ada

Abstract: We describe the automatic generation of a provably correct compiler for a non-trivial subset of Ada. The compiler is generated from an action semantic description; it emits absolute code for an abstract RISC machine language that currently is assembled into code for the SPARC and the HP Precision Architecture. The generated code is an order of magnitude better than what is produced by compilers generated by the classical systems of Mosses, Paulson, and Wand. The use of action semantics makes the processable la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1992
1992
1996
1996

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Our example programs are a bubblesort program (written in both HypoPL and Ada), and programs for performing the sieve of Erathosthenes and the algorithm of Euclid (written in Ada). These programs may be found in Palsberg (1992a).…”
Section: Binding Time Improvementsmentioning
confidence: 99%
“…Our example programs are a bubblesort program (written in both HypoPL and Ada), and programs for performing the sieve of Erathosthenes and the algorithm of Euclid (written in Ada). These programs may be found in Palsberg (1992a).…”
Section: Binding Time Improvementsmentioning
confidence: 99%
“…Additional experiments, see [43], have shown that the code runs at least two orders of magnitude slower than a corresponding target program produced by the C compiler (without optimization). This is somewhat disappointing but still an improvement compared to the classical systems of Mosses, Paulson, and Wand where a slow-down of three orders of magnitude has been reported [22].…”
Section: Performance Evaluationmentioning
confidence: 99%
“…Most definitions and proofs are omitted. For an overview of our experiments with generating a compiler for a subset of Ada, see [43].…”
Section: Introductionmentioning
confidence: 99%
“…As reported in his PhD thesis [58] and papers [57,59] at ESOP and ICCL in 1992, Palsberg has designed, implemented, and proved the correctness of a compiler generator that accepts action-semantic descriptions of imperative programming languages. He has used it to generate compilers for both a toy language and a non-trivial subset of Ada.…”
Section: Provably-correct Compiler Generationmentioning
confidence: 99%